SOME PROBLEMS IN PROPERTY ACCOUNTING. - Himmelblau, David (The Accounting Review, 1928)
Abstract As the capital asset accounts and the reserve for depreciation provided therefore are cumulative from the inception of the business, the auditor analyzes these accounts for the entire period to ascertain how they were built up. This is necessary even though the appraised sound value at the balance sheet date will be used as the basis for issuing securities because errors either in the asset account or in the depreciation reserve also affect the net profits available for interest and dividends. All increase in physical assets is admitted to be an addition or betterment, provided it does not replace a previously existing asset. If it does, it would seem best to retire the old asset and treat the new one as an addition. If a new machine is purchased solely as reserve equipment the question is occasionally raised as to whether it constitute an addition. While it will not increase plant output, it may be expected to avoid delay in production. Cost includes, in case of purchased property, all expenditures required to install the property ready for use, including invoice price, freight and cartage inward, installation expense.